Aktivne vyhl'adávanie geneticky podmienených patologických stavov v detskej populácii okresu Dolný Kubín - Misovicová, N; Srsnová, K (Ceskoslovenska pediatrie, 1993)
In the child population in the district of Dolný Kubín the authors screened during a five-year period children with a suspect genetic aetiology of affections. They examined a total of 1058 children, i.e. 2.34% of the child population in the district. The results were compared with a control group of children examined as a result of previous screening. From their work ensues: 1. 2.34% children aged 0-14 years have indications for genetic examination. 2. The method of an active approach to screening of genetic pathology is ten times more effective than the hitherto used method of detection.
Keywords: genetické nemoci vrozené; mužské pohlaví; Male; Female; Humans; kojenec; lidé; Chromosome Aberrations; ženské pohlaví; chromozomální aberace; Infant; mladiství; Child; dítě; Adolescent; Československo; Genetic Testing; Czechoslovakia; Child, Preschool; genetické testování; Chromosome Disorders; předškolní dítě; Genetic Diseases, Inborn; chromozomální poruchy